Faktor Yang Melatar Belakangi Anak Melakukan Tindak Pidana Pencurian Sepeda Motor Dalam Suatu Negara Yang Pemerintahannya Republik - Moohulao, Fathia Nurul Hasanah; Junus, Nirwan; Mandjo, Julius T. (CV. ITTC INDONESIA, 2023)
Crimes are not only committed by adults, but many crimes are also committed by children. Criminal acts in Indonesia have been regulated in law, both those committed by adults and crimes committed by children. One of the crimes committed by children is the crime of theft. Criminal acts of theft are increasingly being committed by children, often accompanied by aggravating circumstances to make the action easier. Children often look for shortcuts to get an item by stealing and then get money from the sale. The purpose of this research is to find out the factors behind children committing the crime of motorcycle theft, to find out the modus operandi of children in committing the crime of motorcycle theft many times in the city of Gorontalo, to find out the efforts of the police in carrying out countermeasures against the perpetrators of the crime of theft. motorcycle many times by children. The research conducted was normative legal research with a sociological juridical approach taken from primary data by conducting interviews and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study it is understood that the chronology of the incident of the crime of motorcycle theft committed by the case study child at the Gorontalo City Police was due to factors that resulted in the child committing the crime of motorcycle theft in the case including environmental factors, economic factors, and factors of lack of supervision from parents , Modus Operandi is a mode of self-desire and there is an element of adult solicitation. Police efforts in dealing with perpetrators of the crime of motorcycle theft by children are in the form of preventive and repressive efforts.